Peritoneal carcinosis of ovarian origin - Fagotti, Anna (Baishideng Publishing Group Co., Limited, 2010)
Epithelial ovarian cancer (EOC) is the second most common genital malignancy in women and is the most lethal gynecological malignancy, with an estimated five-year survival rate of 39%. Despite efforts to develop an effective ovarian cancer screening method, 60% of patients still present with advanced disease. Comprehensive management using surgical cytoreduction to decrease the tumor load to a minimum, and intraperitoneal chemotherapy to eliminate microscopic disease on peritoneal surface, has the potential to greatly improve quality of life and to have an impact on survival in ovarian cancer patients. Despite achieving clinical remission after completion of initial treatment, most patients (60%) with advanced EOC will ultimately develop recurrent disease or show drug resistance; the eventual rate of curability is less than 30%. Given the poor outcome of women with advanced EOC, it is imperative to continue to explore novel therapies.